BUDDHISTIC CONNOTATIONS IN THE WORKS BY G.GAZDANOV - G A Sorokina (RUDN Journal of Studies in Literature and Journalism, 2016)
The article analyzes the reception and interpretation of Buddhistic ideas in the works by G. Gazdanov - one of the most famous writers of the young generation of Russian literature abroad. The main feature of Gazdanov’s prose lies in the fact that Buddhistic ideas and images are included in the context of Western culture of the XX-th century. Gazdanov applies to such Buddhistic conceptions as ego, reincarnation, karma, illusory of the world and others. These conceptions are represented in a variety of interpretations. The author of the article considers Buddhistic connotations of the works by Gazdanov in the context of his biography and underlines that his Buddhistic ideas and images have philosophical, but not religious character. In Russia the works by Gazdanov became widely known only in the 1990-ies.